Life on earth - Mahon, Derek 1941-2020 (Gallery Books, 2008)
'Life on Earth' is a collection of poetry by Derek Mahon.
Keywords: Englisch; Lyrik; Ökologie; Ecology -- Poetry; Environmental quality -- Poetry